Transformation Temperatures and Electrochemical behavior of Polycrystalline Fe-Doped Ni-Mn-Ga and Co-Ni-Ga Alloys - Sanchez Carrillo, M. (2018)
The effect of Fe addition on martensitic transformation temperatures and electrochemical behavior was studied in polycrystalline Ni51.4Mn24.8-XGa23.8FeX alloys (1˂x˂2.2) and Co38.3Ni32.1Ga29.6 as alternative to Ni-Mn-Ga alloys which are used as ferromagnetic shape memory alloys. The analysis of corrosion rates was conducted by cyclic polarization curves with potentiostat-galvanostat equipment. The corrosion morphologies were also analyzed by scanning electron microscopy (SEM). The kinetics of corrosion was found to decrease with increasing Fe content in the alloy, while the martensitic transformation temperatures increased with increasing Fe content. The Co38.3Ni32.1Ga29.6 alloy shows icorr lower than the Ni-Mn-Ga alloy. From results, the studied alloys exhibited a general dissolution in the anodic branch where a spontaneous passive zone occurred at certain potential and some elements like Co, Mn and also Ni were present in a higher percentage in corrosion deposits.